Pemetaan Potensi Wisata Bahari sebagai Dasar Pengembangan Destinasi Pesisir di Kecamatan Karamat, Kabupaten Buol - Ariani Ariani; Sunarty Suly Eraku; Sri Maryati (Universitas Negeri Gorontalo, 2026)
Karamat District has several marine tourism destinations with the potential to support coastal tourism development. This study aims to identify the spatial distribution of marine tourism destinations, evaluate the potential level of each destination, and formulate development priority directions using Quantum GIS (QGIS). A descriptive quantitative method with a spatial analysis approach was employed. Data were collected through field observations, structured interviews, coordinate recording, satellite imagery, and administrative base maps. The potential assessment was conducted using 31 indicators covering tourism attractions, accessibility, supporting facilities, coastal environmental conditions, and community socio-economic support. The results identified four major destinations, namely D'Moanga Beach, Tanjung Dako Beach, Tanjung Manis Beach, and Busak Island. Based on the scoring results, D'Moanga Beach was classified as having very high potential with an average score of 4.26, Tanjung Dako Beach as having high potential with a score of 3.65, while Tanjung Manis Beach and Busak Island were categorized as having moderate potential with scores of 3.31 and 2.85, respectively. QGIS-based mapping effectively visualized the spatial distribution of tourism destinations and supported the determination of development priorities according to the characteristics and needs of each location. The findings indicate that a spatial approach can serve as a valuable basis for formulating more targeted and potential-based marine tourism development strategies.